Vegetation response to grazing pressure in the Puna flat, NW Argentina - Quiroga Mendiola, Mariana; Tálamo, Andrés (University of Kentucky, 2025)
Puna grasslands are located at a high‐altitude flat plateau in the Northwest of Argentina. It is an arid territory (100 to 300 mm rainfall/year) at 3,000 to 4,000 m a.s.l. The vegetation is scarce, where Andean pastoralist communities produce meat and wool, specialized in llama (Lama glama) and sheep‐breeding, although they do breed multi‐species herds that may also include goats and cattle. There are erosion processes in the Puna, where shepherds and their animals could be synergetic factors with natural very hard climatic conditions. In this work we assess the effect of ovine and lama grazing on the plant communities in the Puna grasslands. Considering that stockyards are used in a very complex way along the year, having differences between those used in winter or in summer, or used for many months or only one month, etc. we built up a Grazing Pressure Index taking in account all these factors in each sampling point. We sampled 28 paired transects (14 in sites with high grazing pressure, and 14 in sites with low grazing pressure) in 2 different ecological sites (grassy grassland and shrubby steppe). Focusing our work on the community functionality, we analysed Plant Functional Types (PTF) measuring their cover, richness and diversity. Our results do not show significant differences on PFT cover, richness or diversity between sites at different grazing pressures. It could be the result of a low grazing pressure or a long grazing pressure history that had configured the TFP associations.